FAKTOR EKONOMI YANG MEMPENGARUHI CAPITAL FLIGHT DI NEGARA BERKEMBANG ANGGOTA ASEAN - Lilis Hoeriyah; Indra Suhendra; Samsul Arifin (Jurnal Ekonomi-Qu, 2019)
This research aims to analyze the impact of Gross Domestic Product (GDP), Real Effective Exchange Rate (REER), differences in interest rates and inflation on capital flight in eight developing countries of ASEAN regions. This research uses secondary data during the periods of 2007-2016. The research methodology used in this study is panel data regression with FEM(Fixed Effect Model). The results of this research show that simultaneously, Gross Domestic Product (GDP), Real Effective Exchange Rate (REER), differences in interest rates and inflation have significant impact on capital flight. Partially, all of variables have significant positive impact on capital flight. However, the variable of REER shows insignificant to capital flight.